2020
DOI: 10.1002/art.41423
|View full text |Cite
|
Sign up to set email alerts
|

Altered Properties of Endothelial Cells and Mesenchymal Stem Cells Underlying the Development of Scleroderma‐like Vasculopathy in KLF5+/−;Fli‐1+/− Mice

Abstract: Objective In prevous studies, we established a new animal model, KLF5+/−;Fli‐1+/− mice, in which fundamental pathologic features of systemic sclerosis (SSc) are broadly recapitulated. SSc vasculopathy is believed to occur as a result of impaired vascular remodeling, but its detailed mechanism of action remains unknown. To address this, the present study investigated the properties of dermal microvascular endothelial cells (DMECs), bone marrow–derived endothelial progenitor cells (BM‐EPCs), and bone marrow–deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Moreover, Fli1 haploinsufficiency has been found to induce a profibrotic phenotype in dermal ECs of bleomycin-treated mice, further strengthening the involvement of this transcription factor in EndoMT during the development of cutaneous fibrosis [ 57 , 58 ]. Recently, dermal ECs explanted from KLF5+/−; Fli1+/− mice, a new animal model resembling the fundamental pathologic features of SSc, were reported not only to be defective in performing in vitro angiogenesis, but also to have a reduced expression of VE-cadherin and CD31, suggesting the occurrence of EndoMT, as observed in SSc-affected ECs, and highlighting that a deficiency of KLF5 transcription factor may be another important trigger of this process [ 59 ]. SSc-related EndoMT has been recently found to be induced also by oncostatin M, a member of the IL-6 family, and the inflammatory lipid mediator leukotriene B4, whose expression levels are increased in SSc [ 60 , 61 ].…”
Section: The Pathogenic Role Of Vascular Wall-resident Cells In Systemic Sclerosis: Linking Vasculopathy To Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Fli1 haploinsufficiency has been found to induce a profibrotic phenotype in dermal ECs of bleomycin-treated mice, further strengthening the involvement of this transcription factor in EndoMT during the development of cutaneous fibrosis [ 57 , 58 ]. Recently, dermal ECs explanted from KLF5+/−; Fli1+/− mice, a new animal model resembling the fundamental pathologic features of SSc, were reported not only to be defective in performing in vitro angiogenesis, but also to have a reduced expression of VE-cadherin and CD31, suggesting the occurrence of EndoMT, as observed in SSc-affected ECs, and highlighting that a deficiency of KLF5 transcription factor may be another important trigger of this process [ 59 ]. SSc-related EndoMT has been recently found to be induced also by oncostatin M, a member of the IL-6 family, and the inflammatory lipid mediator leukotriene B4, whose expression levels are increased in SSc [ 60 , 61 ].…”
Section: The Pathogenic Role Of Vascular Wall-resident Cells In Systemic Sclerosis: Linking Vasculopathy To Fibrosismentioning
confidence: 99%
“…Furthermore, prolonged exposure of BM-MSCs to a profibrotic milieu mimicking the SSc microenvironment increased the tendency of these cells to differentiate into myofibroblasts [ 98 ]. Finally, similarly to human SSc BM-MSCs, it has been reported that also BM-MSCs from the KLF5+/−; Fli1+/− murine model of SSc display enhanced migration, proliferation and collagen production in response to TGF-β1, thus showing a preferential differentiation toward myofibroblasts instead of behaving as pericyte precursors [ 59 ].…”
Section: The Pathogenic Role Of Vascular Wall-resident Cells In Systemic Sclerosis: Linking Vasculopathy To Fibrosismentioning
confidence: 99%
“…Recently, in an experimental model of SSc, the double heterozygous mice for Klf5 and Fli1 (Klf5 +/− ; Fli1 +/− ), showing the three main pathological characteristics of SSc [159], the dermal microvascular ECs isolated from these mice, show defective angiogenesis and reduced expression of VE‐cadherin and CD31, confirming the evidence of EndMT in this SSc model [160].…”
Section: Evidence Of Endmt During Human Sscmentioning
confidence: 67%
“…These vascular alterations are caused by dysregulated angiogenesis and defective vasculogenesis. FLI1 deficiency is a key disease factor regulating a broad spectrum of endothelial behaviors and vascular remodeling associated with SSc vasculopathy, including angiogenesis and vasculogenesis [ 45 ]. FLI1 deficiency suppresses the expression of CD31, VE-cadherin, S1P 1, and platelet-derived growth factor-B in endothelial cells, while upregulating matrix metalloproteinase-9, resulting in vascular destabilization and angiogenesis [ 29 ].…”
Section: Discussionmentioning
confidence: 99%